Joint advertising of complementary products sold through an independent retailer. Issue 15 (3rd August 2018) - Karray, Salma; Sigué, Simon Pierre
Abstract : Two game-theoretic models are developed to study the profitability of joint advertising in a context where two manufacturers sell complementary products through an independent retailer and can either advertise separately or jointly. We find that it may not be in the interest of symmetric manufacturers to partner for advertising, especially when joint advertising is less effective than firms' individual advertising and the degree of advertising complementarity between the two products is high. Conversely, the manufacturers prefer joint advertising to individual advertising programs even if its effectiveness is lower, but both the degrees of price and advertising complementarity are very large. Under these conditions, joint advertising is implemented at the expense of the retailer who suffers from the associated reduced demand for the two products. In such a context, the manufacturers' advertising partnership mainly reduces advertising costs by mitigating double marginalisation in pricing. The extension to asymmetric manufacturers shows that the weaker manufacturer and the retailer can induce the stronger manufacturer to engage in joint advertising.